PROSES PENGOLAHAN DAN KUALITAS AIR MINUM DI KOMPLEKS PERUMAHAN KARYAWAN PT. CHEVRON PACIFIC INDONESIA (PT. CPI) DURI-RIAU TAHUN 2014 - Mia Yulianty; evi naria; surya dharma (Lingkungan dan Kesehatan Kerja, 2014)
Water is one of the important matter after the air, nobody can life without drinking until 4-5 days. Drinking water which is not qualified, can resulting disease or even death. Water treatment can prevents disease and resulting qualified drinking water. PT. Chevron Pacific Indonesia (PT. CPI) is one of the companies which has a water treating plant to makes drinking water from raw water The purpose of this research is to know the process of water treatment, the quality of raw water after treatment and quality of distributed drinking water to employees housing PT. Chevron Pacific Indonesia Duri. This research was descriptive survey using simple random sampling technique with 1102 populations and 30 samples. Data were analyzed descriptively in tabulation and narration. The result of the research showed that the water treatment was using coagulation, floculation, sedimentation and desinfectan process. Based on the analysis of obtaained data, the quality of raw water was qualified, whereas the quality of water which was finish the treatment and the quality of distributed drinking water to employees housing on Maret 2014 were not qualified in one parameter. Most of the respondents have been using water as drinking water. The conclusion of this research is the water treatmen process in PT. Chevron Pacific Indonesia was conventional water treatment (complete water treatment). Overall water quality is good, it is recommended to improve adsorption using activated carbon, renew and re-examine the tools used and provision of information about water quality to water users. Keyword : Water drinking, Water Treatment, Water quality